The lobster tale: an exercise in critical thinking. - Stepanovich, Paul L (Journal of Management Education, 2009)
Professors in management and business are encouraged to incorporate critical thinking as an objective in their courses. "The Lobster Tale" provides an opportunity to engage students in various levels of critical thinking, ranging from a relatively superficial reading to an examination of the deeper, often hidden issues. Using the foundations of critical theory and systems theory, the story draws on economics, social theory, philosophy, and other disciplines to present a simplified version of the complexities found in our global environment. It can be used to supplement a variety of courses in the business curriculum and to encourage students to challenge not only assumptions but also conventional wisdom and, perhaps, knowledge itself. © 2009 The Author(s).
Keywords: Affirmative action; Critical theory; Critical thinking; Systems theory; Tragedy of the commons; dept.mgt

Using system dynamics to illustrate deming’s system of profound knowledge - Stepanovich, Paul L (Total Quality Management & Business Excellence, 2004)
This article presents a systems dynamics model to illustrate some of the aspects of Deming's System of Profound Knowledge. As a pedagogical tool, it would serve as a useful introduction for those new to Deming's ideas. It not only introduces the main parts of his system, but also highlights their interconnectedness. The model environment, an interactive management flight simulator, and the model content combine to provide several learning opportunities. The model uses the assumptions of regression to the mean, the 80:20 Rule, random walks, and learned helplessness to present a theory of how, managers learn to reduce quality in organizations. Those interested in exploring or teaching Deming's System can use the model as a launching point from which to explore the system further. Running the simulation provides an opportunity to identify and challenge assumptions, explore the harmful effects of tampering, examine the fundamental attribution error, develop control charts, and challenge the application of behaviourism in management.
Keywords: Deming; Pedagogy; Quality; System dynamics; dept.mgt